Gambaran Psikologis Mahasiswa Laki-Laki Penyuka Anime Genre Yaoi (Fudanshi) di Kota Makassar - Saffana Mustafani; Ahmad Ridfah; Sitti Hadjar Nurul Istiqamah (CV. Ulil Albab Corp, 2023)
Fudanshi is a male fan of yaoi (Boy's love) anime. Fudanshi realize that their liking is a taboo in society, but still watch yaoi anime because they have various reasons, both from the psychological aspect of fudanshi, and from the closest people to fudanshi. This study aims to see the psychological picture and background of people around from fudanshi. The research method used in this research is qualitative with a case study approach. The data collection technique used in this research was interviews of one male student aged 19 years. The results of the research show that family background influences respondent to know and watch yaoi anime. From the cognitive aspect, in the form of views towards the yaoi anime, which does not have a big difference from other anime genres, from the affective aspect, there are feelings of fear and sadness regarding the public's response, while in terms of conation, there are changes in behavior before dan after getting to know the yaoi anime. The results of this research can be a source of information regarding the psychological picture of individuals who like the yaoi anime.